Relationship Lending and Firms' Leverage: Empirical Evidence in Europe. (5th December 2016) - Guida, Roberto; Sabato, Valentina
Abstract: Using a novel measure of relationship lending based on the kind of information banks use to assess borrowers, we investigate the role of relationship lending in firms' capital structure. Using a unique dataset of European manufacturing firms, we measure relationship lending based on three dimensions (closeness, soft information, exclusivity) and relate them to firms' leverage. Overall our results support the hypothesis that supply factors matter. We find that the actual use of soft information increases leverage and only firms without soft information‐intensive relationships increase their leverage through multiple relationships. However, the effect of relationship lending on leverage varies across countries.